2018
DOI: 10.1016/j.amsu.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of gallstone sigmoid ileus management

Abstract: IntroductionGallstone sigmoid ileus is a rare although serious complication of cholelithiasis resulting in large bowel obstruction. The condition accounts for 4% of all gallstone ileus patients. There are no recognized management guidelines currently. Management strategies range from minimally invasive endoscopy and lithotripsy to substantial surgery. We aim to identify trends when managing patients with gallstone sigmoid ileus to help improve outcomes.MethodsLiterature searches of EMBASE, Medline and by hand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 53 publications
0
44
0
4
Order By: Relevance
“…5 Gallstone ileus more commonly found at 65 years rather than under 50. 3,6 Gallstone ileus in the young patient was reported by Chatterjee (2008). 7 The youngest those reported was 13 years old while the oldest was 91 years old.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…5 Gallstone ileus more commonly found at 65 years rather than under 50. 3,6 Gallstone ileus in the young patient was reported by Chatterjee (2008). 7 The youngest those reported was 13 years old while the oldest was 91 years old.…”
Section: Discussionmentioning
confidence: 90%
“…9,10 Diarrhoea in the first case is unusually found. 6 However, it can be explained by bile acid overflow through bile-enteric fistula at the terminal ileum. 11,12 Mild hyponatremia in the first case related to vomiting and diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Gallstone ileus accounts for ~1–4% of intestinal obstruction cases, with the occlusion occurring mostly in the terminal ileum or the ileocecal valve [ 5 ]. This condition is associated with high morbidity and mortality [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colonic biliary ileus is even scarcer, with the majority of cases reporting sigmoid obstruction. Farkas et al [ 5 ] have recently reported a wide array of surgical interventions that have been previously used to manage gallstone sigmoid ileus, including enterolithotomy, caecostomy, Hartmann’s procedure and bowel resection. Non-surgical measures such as endoscopy and lithotripsy have also been described [ 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation